Hubungan Loneliness Dengan Kecenderungan Smartphone Addiction Pada Mahasiswa Psikologi - Katarina Gelu Dasilva (PT. Hasba Edukasi Mandiri, 2026)
Among university students, the phenomena of loneliness and smartphone addiction have become increasingly prevalent issues. Students are in a transitional stage toward adulthood, where they face various academic demands, social adjustment processes, and separation from their families and home environments. These conditions often lead to feelings of insecurity or isolation, especially among freshmen and students who live away from home. As a coping strategy, many students utilize smartphones as a means of entertainment, communication, and social interaction through social media, online games, and instant messaging applications. This study employed a quantitative method with a purposive sampling technique. The sample consisted of 95 psychology students from Universitas 17 Agustus 1945. The measurement instruments used in this study were a Likert scale of smartphone addiction developed by Ghaida (2019), which adapts the Smartphone Addiction Scale: Development and Validation of a Short Version for Adolescents by Kwon et al. (2013), and a loneliness scale developed by Schermer & Martin (2019). Data analysis techniques included assumption testing and hypothesis testing using SPSS version 29.0 for Windows. The results showed that loneliness is significantly associated with smartphone addiction, indicating a positive relationship between the two variables. Thus, the higher the level of loneliness experienced by students of Universitas 17 Agustus 1945 Samarinda, the higher the tendency toward smartphone addiction (r = 0.214; p = 0.043). However, the strength of this relationship is considered low, with a coefficient of determination of 0.046, meaning that loneliness contributes only 4.6% to smartphone addiction.